Accreditation of primary health care services: A systematic review - Babak Rastegarimehr; Ahmad Ahmadi Teymourlouy; Hasan Abolghasem Gorji (Journal of Education and Health Promotion)
Accreditation of health services is one of the criteria for achieving the predetermined standards for health organizations. Therefore, the purpose of this systematic study was to investigate the primary health care (PHC) accreditation programs in the world and compile a summary of these programs in order to identify the areas and dimensions of these standards. This systematic review was conducted on online database studies, including PubMed, Scopus, Web of Science, and Google Scholar, using comprehensive terms. The inclusion criteria included all qualitative, quantitative, and mixed-method studies published in any language from 1990 to December 2022. The studies were evaluated with Joanna Briggs Institute Critical Appraisal Tools (JBI) critical appraisal tools checklist, and finally, the data were analyzed using the framework analysis method. The findings of 10 studies that were included in this study cover four main topics regarding the functions of the health system: stewardship, resource production, financing, and service delivery, as well as 10 sub-topics: policy making, interdepartmental leadership, monitoring and evaluation, human resources, equipment and medicine, information management, gathering of financial resources, capacity to provide services, access, and quality of services. In the accreditation of PHC, in addition to paying attention to performance indicators, indicators such as satisfaction and rights of clients and employees, access, information technology, coordination, integration of care, financing, and management of resources and equipment should also be considered.